IMPLEMENTASI NADZOM KUNCI NAHWU (NKN) DALAM PEMBELAJARAN NAHWU UNTUK MENINGKATKAN PEMAHAMAN SANTRI DI MADRASAH DINIYAH PUTRI BABUSSALAM PAGELARAN MALANG - Alfi Nur Laili, Alif Achadah (JIPI (Jurnal Ilmiah Pendidikan Islam), 2025)
This research is motivated by the low level of students' understanding of Nahwu (Arabic grammar) at Madrasah Diniyah Putri Babussalam, which is attributed to the use of traditional teaching methods that lack engagement and the students’ limited mastery of the Arabic language, particularly in reading classical Islamic texts (kitab kuning). As an alternative solution, the Nadzom Kunci Nahwu (NKN) method was implemented, a summarized version of the Jurumiyah text presented in 150 poetic stanzas in the Indonesian language, structured into ten stages of learning through a prefix-suffix approach. This study employed a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The findings indicate that the application of NKN has had a positive impact on enhancing students’ learning motivation, memorization skills, and comprehension of Nahwu and classical texts. However, challenges remain, such as a reliance on rote memorization and limited grammatical understanding if not supported by supplementary analytical methods.